2009
DOI: 10.1007/s12223-009-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirulent E. coli in inflammatory and noninflammatory bowel diseases

Abstract: We determined the incidence of enterovirulent E. coli (EVEC; which can to cause gastrointestinal infections) in strains isolated from patients with both of the major inflammatory bowel diseases (IBD), Crohn's disease (CD) and ulcerative colitis (UC) and from patients with noninflammatory bowel diseases (nonIBD). Cell detachment E. coli (CDEC) were detected in 14 % of all strains. A significant difference in the presence of CDEC was found between the groups of strains isolated from UC (24.1 %), nonIBD (11.9 %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Template DNA was extracted by the boiling-water method [17]. All E. coli strains were screened for presence of genes encoding toxins by a simplex and multiplex PCR assays using specific primers in appropriate conditions (Table 1).…”
Section: Virulence Factor Genesmentioning
confidence: 99%
“…Template DNA was extracted by the boiling-water method [17]. All E. coli strains were screened for presence of genes encoding toxins by a simplex and multiplex PCR assays using specific primers in appropriate conditions (Table 1).…”
Section: Virulence Factor Genesmentioning
confidence: 99%
“…EIEC and STEC were not found in collected samples. 17 Moreover, EAEC was detected in 2.5%, EPEC in 1.3% and ETEC in 1.5% of all IBD E. coli isolates in the study of Cǔrová et al The authors concluded that their low incidence was in agreement with the fact that they are associated with diarrhea, not to other GIT diseases, 18 while other studies found that all E. coli IBD isolates were negative for intestinal genes. 5,6 They justified the very low detection rate of classical E. coli intestinal genes by the previous observations confirming that E. coli from IBD patients are more closely related to ExPEC.…”
Section: Antimicrobial Susceptibility Resultsmentioning
confidence: 89%
“…Malignancy gene profiles are inextricably related to the evolutionary origin of the strain 47 . Where B2 and D are predominant in patients with IBD, more commonly discovered virulence-linked genes indicative of ExPEC were found in IBD patients than in controls, depending on the abundance of phylogenetic groups, and without differences in other investigation types 50 . A shift in the phylotype distribution would result in increased abundance of E. coli with colonization factors, facilitating fixation and persistence in IBD patients.…”
Section: Pathogenic Properties Of E Colimentioning
confidence: 93%
“…Although inspecific genetic characteristics separate E. coli from the UC or CD gut mucosa, certain virulence factors have been discovered that are distributed variably amongst these IBD types. For instance, diarrhea-linked hemolytic E. coli, also known as cell-detaching E. coli (CDEC), has been detected in about 24 % of UC E. coli patients, while detected in only 4.7 % of CD E. coli patients 50 . Diarrhea-linked hemolytic E. coli usually carries pilus P, hemolysin, S-fimbria genes, and cytotoxic necrotizing factor 1.…”
Section: Pathogenic Properties Of E Colimentioning
confidence: 99%
See 1 more Smart Citation